2006
DOI: 10.1111/j.1600-0749.2006.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies of melanogenesis: the influence of N‐substitution on dopamine quinone cyclization

Abstract: The influence of side-chain structure on the mode of reaction of ortho-quinone amines has been investigated with a view, ultimately, to developing potential methods of therapeutic intervention by manipulating the early stages of melanogenesis. Four N-substituted dopamine derivatives have been prepared and quinone formation studied using pulse radiolysis and tyrosinase-oximetry. Ortho-quinones with an amide or urea side chain were relatively stable, although evidence for slow formation of isomeric para-quinomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…Our results are consistent with recent studies that show that in urea or carbamate derivatives of dopamine the nitrogen atom is not sufficiently nucleophilic to effect the necessary cyclization that results in release of the antitumour agent [21,22]. …”
Section: Figure 1 Near Heresupporting
confidence: 93%
“…Our results are consistent with recent studies that show that in urea or carbamate derivatives of dopamine the nitrogen atom is not sufficiently nucleophilic to effect the necessary cyclization that results in release of the antitumour agent [21,22]. …”
Section: Figure 1 Near Heresupporting
confidence: 93%
“…NAcetyldopamine can serve as a substrate for tyrosinase; thus, the long-chain N-acyldopamines could also be oxidized to a quinone by this enzyme [46]. N-Acetylnoradrenaline is a known human metabolite [47] suggesting that N-acetyldopamine and the longer-chain Nacyldopamines could serve as substrates for dopamine β-monooxygenase.…”
Section: N-acyldopaminesmentioning
confidence: 99%
“…In contrast to the urea 44, the thiourea 47 cyclises (k d 1.7 s -1 at pH 8.0) to give the bicyclic derivative 48. 3 Clearly the thiourea suphur is a good nucleophile and the rate of seven-membered ring formation is comparable to that observed for the corresponding secondary amines 33 (Table 3). …”
Section: Methodsmentioning
confidence: 48%
“…The amide 43 and the urea 44 showed no tendency to cyclise and were stable over the pulse radiolysis timescale. 3 However, combined oximetry and spectrophotometry studies showed evidence of first order isomerisation, with well-defined isosbestic points, giving the para-quinomethanes 45 and 46. These ortho-quinone to paraquinomethane rearrangements were found to have rate constants k d ≈ 0.004 s -1 (amide) and k d ≈ 0.0002 s -1 (urea) at pH 7.4.…”
Section: Other Substituentsmentioning
confidence: 99%
See 1 more Smart Citation